1996
DOI: 10.1002/aic.690420713
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and concentration on column dynamics of weak electrolyte ion exchange

Abstract: The column dynamics of simple ion-exchange processes involving acetic acid and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
2
10
0
Order By: Relevance
“…Jansen et al (1996) showed that this is at variance with experiment. The second and the third approach do allow penetration of coions into the ion exchanger and are about equally good in describing the experimental results of Jansen et al (1996). In this article we use the second approach.…”
Section: Pore Liquidmentioning
confidence: 68%
See 1 more Smart Citation
“…Jansen et al (1996) showed that this is at variance with experiment. The second and the third approach do allow penetration of coions into the ion exchanger and are about equally good in describing the experimental results of Jansen et al (1996). In this article we use the second approach.…”
Section: Pore Liquidmentioning
confidence: 68%
“…(For convenience we will assume that there are pores in the interior of ion exchange particles, although many ion exchangers consist of a polymer network that contains no real pores.) Jansen et al (1996) compared three approaches to describe the adsorption of small ions to ion exchangers: the SMA model with the pore liquid as part of the adsorbing phase; the SMA model with the pore liquid as part of the liquid phase; and the Donnan equilibrium with the pore liquid as part of the adsorbing phase.…”
Section: Pore Liquidmentioning
confidence: 99%
“…The complete exclusion of co-ions is rarely achieved in reality, and this assumption leads to inaccuracies in the estimation of species concentrations in the resin phase [4]. There have been efforts to relax this assumption and develop more broadly applicable models [8][9][10][11][12][13], however, these models still rely on adjustable parameters that must be fit to experimental data. Jansen et al [8] visualize the resin as a homogeneous phase in which the active sites are randomly distributed and uses a Donnan approach to estimate pH of the resin phase.…”
Section: Introductionmentioning
confidence: 99%
“…The stoichiometric relationship may [1][2][3]6] or may not [7][8][9][10][11] be incorporated into the model to account for interactions between mobile species and resin fixed-charge sites. When the stoichiometric relationship is not included, the phase equilibrium is usually seen to be described by means of an equilibrium constant [7] or selectivity factor [9][10][11]. Many of these models assume that coions are essentially excluded from the resin phase due to Donnan equilibrium forces [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation